Enantioselective synthesis of (S)-timolol via kinetic resolution of terminal epoxides and dihydroxylation of allylamines - Narina, Srinivasarao V.; Sudalai, Arumugam (Tetrahedron, 2007)
An efficient enantioselective synthesis of (S)-timolol has been described using chiral Co-salen-catalyzed kinetic resolution of less expensive (+/-)-epichlorohydrin with 3-hydroxy-4-(N-morpholino)-1,2,5-thiadiazole in good overall yield (55%) and excellent enantioselectivity (98%). Synthesis of (S)-timolol has also been achieved using hydrolytic kinetic resolution as well as asymmetric dihydroxylation routes in 90% ee and 56% ee, respectively. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: asymmetric reactions; diols; epoxides; Kinetic resolution; oxazolidinone